Electronic Structure of MnSi1,7 Po Dannim Mossbauer Spectroscopy - Ziyanova Sayora Ibragimovna; Turaev Ergash Yuldashovich (Genius Journals, 2022)
In the present work, a Messbauer study of the MnSi1.7 compound on impurity iron and tin atoms was undertaken. These atoms isomorphically substitute for manganese and silicon, respectively, and therefore it is possible to determine the electronic structure of Mn and Si atoms from the parameters of the 57Fe, 119Sn Messbauer spectra
Keywords: Magnesium; silicon; spectrum; glands